Diagnostic tests for primary renal hypouricemia - Sebesta, Ivan; Stiburkova, Blanka; Bartl, Josef; Ichida, Kimiyoshi; Hosoyamada, Makoto; Taylor, Judy; Marinaki, Anthony (Nucleosides, nucleotides & nucleic acids, 2011)
Primary renal hypouricemia is a genetic disorder characterized by defective renal uric acid (UA) reabsorption with complications such as nephrolithiasis and exercise-induced acute renal failure. The known causes are: defects in the SLC22A12 gene, encoding the human urate transporter 1 (hURAT1), and also impairment of voltage urate transporter (URATv1), encoded by SLC2A9 (GLUT9) gene. Diagnosis is based on hypouricemia (<119 μmol/L) and increased fractional excretion of UA (>10%). To date, the cases with mutations in hURAT1 gene have been reported in East Asia only. More than 100 Japanese patients have been described. Hypouricemia is sometimes overlooked; therefore, we have set up the flowchart for this disorder. The patients were selected for molecular analysis from 620 Czech hypouricemic patients. Secondary causes of hyperuricosuric hypouricemia were excluded. The estimations of (1) serum UA, (2) excretion fraction of UA, and (3) analysis of hURAT1 and URATv1 genes follow. Three transitions and one deletion (four times) in SLC22A12 gene and one nucleotide insertion in SLC2A9 gene in seven Czech patients were found. Three patients had acute renal failure and urate nephrolithiasis. In addition, five nonsynonymous sequence variants and three nonsynonymous sequence variants in SLC2A9 gene were found in two UK patients suffering from acute renal failure. Our finding of the defects in SLC22A12 and SLC2A9 genes gives further evidence of the causative genes of primary renal hypouricemia and supports their important role in regulation of serum urate levels in humans.
Keywords: Young Adult; Diagnostic Techniques and Procedures; Organic Anion Transporters; mutace; Renal Tubular Transport, Inborn Errors; Organic Cation Transport Proteins; mladý dospělý; proteiny přenášející organické kationty; diagnostické techniky a postupy; Adolescent; Adult; Aged; dospělí; senioři; vrozené poruchy tubulárního transportu; mladiství; Urinary Calculi; proteiny usnadňující transport glukosy; močové kameny; lidé; Humans; Mutation; Glucose Transport Proteins, Facilitative; lidé středního věku; Middle Aged; přenašeče organických aniontů